Educação do campo e seus desafios em classes multisseriadas: um estudo no contexto da escola São Sebastião em Barcarena-PA - SOUZA, Elder Martins (2021)
The education of the Field is nothing more than a specific school education that provides opportunities for the Field within its specificities and ensures the permanence of subjects in the place where they live. In this context, the teaching in multigrade classes present in the Field contemplates everyone equally, in order to obtain a good learning? Moreover, it aims to know if learning occurs in view of the complexity of the classes, specifically with fifth graders. In order to deepen the theme approached the research aimed to know how learning occurs in a multiseriate class in the community school São Sebastião, in the municipality of Barcarena-Pará. Aiming to understand the way of teaching, school performance and the challenges that teachers and students face this form of teaching in the Field education. The presented results occurred through the qualitative and quantitative research, where it was possible to use the following instruments for the data collection as: semi-structured interviews and application of questionnaire with teacher and student. Data collection occurred with only one teacher and five fifth graders. The research consisted of two stages: the bibliographic research where it was possible to consult the theoretical framework of authors such as Arroyo (2013), Barros (2010), Ferreira (2011) and Hage (2008) among others that portray the theme of rural education. And multigrade classes and Field research. Thus, the results indicate that the teaching in these classes is not of quality due to the fact that it presents several different classes and levels of learning as well as the age-grade distortion. The school has no pedagogical coordination and it became evident that it needs more teacher training. In this sense, the school needs to have a pedagogical political project that meets the realities of rural students in the context in which they live, providing permanence in school and thus obtaining a good performance in studies. The research also revealed that the ownership of school teaching to the family has done little at home to contribute to student learning.